Tolerance of two anhydrobiotic tardigrades Echiniscus testudo and Milnesium inceptum to hypomagnetic conditions - Erdmann, Weronika; Idzikowski, Bogdan; Kowalski, Wojciech; Kosicki, Jakub Z.; Kaczmarek, Łukasz (PeerJ, 2021)
The open space is a hostile environment for all lifeforms not only due to vacuum, high radiation, low atmospheric pressure, and extremely low temperature, but also the absence of the geomagnetic field. The geomagnetic field protects Earth mainly from corpuscular radiation, that is, solar wind and cosmic radiation, but above all it influences organisms, including their cells, tissues and organs. Moreover, numerous studies conducted on plants and animals confirmed that hypomagnetic conditions (the term referring to all situations when the magnetic field is weaker than the typical geomagnetic field) have significant influence on the metabolism of living organisms. Although many studies dealt with a variety of aspects related mainly to the influence of hypomagnetic conditions on human health. Very few studies have considered the influence of hypomagnetic conditions on extremophiles. Astrobiologists have long been testing different extremofiles to find out if any multicellular organisms are able to survive in extreme conditions of open space. Among all multicellular extremophiles fit for such research, water bears (Tardigrada) are the most interesting. Not only are they one of the most resistant organisms on Earth, but results obtained from studies on these invertebrates can be extrapolated or applied to vertebrates (including humans). Despite this, studies on the influence of hypomagnetic conditions on tardigrades are rare, so far. In the present study, to test the influence of hypomagnetic conditions on the process of anhydrobiosis while entering and returning from anhydrobiosis, we used two terrestrial anhydrobiotic species that are Echiniscus testudo and Milnesium inceptum. To exclude the ambient magnetic field, experiments were carried out in a special magnetic field shielding chamber. In total, three experiments were conducted: (a) tardigrades in anhydrobiosis, (b) tardigrades entering anhydrobiosis and (c) tardigrades returning to active life. The obtained results clearly showed that even partial isolation from the geomagnetic field, that is, hypomagnetic conditions, has negative influence on anhydrobiotic abilities of both tested tardigrade species. In both species we observed lower survivability rate while entering anhydrobiosis, in anhydrobiotic state and returning to the active state. What is more, we observed a higher mortality rate in Ech. testudo than Mil. inceptum which suggest that different species response to the hypomagnetic conditions in different way. In conclusion, while current knowledge on the influence of hypomagnetic conditions on mortality of invertebrates is very limited, our results suggest that the presence of the magnetic field is a very important factor which should be considered in further research focused on potential survival of Earth organisms in outer space, spacecrafts or different planets and moons.
Keywords: Extremophiles; Geomagnetic field; Geomagnetobiology; Invertebrates; Astrobiology; Dehydratation; Magnetic field